2020
DOI: 10.1136/bmjopen-2020-041428
|View full text |Cite
|
Sign up to set email alerts
|

Adults’ experiences of living with pulmonary hypertension: a thematic synthesis of qualitative studies

Abstract: ObjectivesPulmonary hypertension is a life-shortening disease that has a considerable impact on quality of life. Improving our understanding of how individuals are affected and cope with the disease will help to improve services and outcomes. This review synthesises the published qualitative research that has listened to adults discuss their experiences of living with the disease.DesignA comprehensive systematic search of four databases was conducted in May 2020: Web of Science, PubMed, PsycINFO and Cochrane L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 55 publications
0
35
0
1
Order By: Relevance
“…This may include increased psychological distress, preference for invasive treatments, greater sick role behaviour, and restriction of independence ( 11 14 ). Additionally, research indicates the impact of a label is diverse and varies depending on your perspective as an individual labelled ( 15 , 16 ), family/caregiver ( 15 , 17 , 18 ), or healthcare professional ( 15 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…This may include increased psychological distress, preference for invasive treatments, greater sick role behaviour, and restriction of independence ( 11 14 ). Additionally, research indicates the impact of a label is diverse and varies depending on your perspective as an individual labelled ( 15 , 16 ), family/caregiver ( 15 , 17 , 18 ), or healthcare professional ( 15 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Highlight the approved effectiveness of the studied intervention, the individually tailored physiotherapy program added to stable target medical therapy, in patients with PAH to maintain the opportunity to participate in activities related to frequency of social contacts in follow-up should be done in the face of PAH as a long-term disease. At the same time, in our study, no substantial deterioration or differences between groups were found in the IPA subscale SL that mainly describes the quality of social relationships, which can be explained by the relatively older age of the participants, and it is highly possible that other issues arise in younger patients, as current evidence from qualitative research suggests that quality concerns of social life would be more relevant in younger patients with PAH as well as in patients with less time after confirmation of diagnosis [ 3 ]. Recognizing that social participation, for example, meeting friends, volunteer work, club activities, and quality of social relationships, described as sense of belonging, respect, inclusion, are important predictors of well-being in persons living with long-term health problems [ 32 ], interventions to support participation are highlighted as relevant part of the interdisciplinary treatment approach.…”
Section: Discussionmentioning
confidence: 67%
“…Besides, Rawling et al (2020) in the synthesis of qualitative studies on the experience of adult patients living with PH described four main topics, one of which emphasized the transitional nature of PH. Coming to the stage with the aim of stabilizing the disease, maintaining a good quality of life and survival, the person faces the challenge of finding a balance between restrictions, a sense of loss, and an attempt to live a previous life despite the exacerbation of symptoms and possible worsening, while forming a new identity and life [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations